Improving Students’ Writing Skills In Narrative Text By Using Semantic Mapping. - Nani Puspita Sari (IKIP PGRI Bojonegoro, 2015)
This research was conducted in order to investigate whether semantic mapping was able to improve studentsâ€™ writing skill of the eleventh grade students of SMA Negeri 2 Cepu or not. The researcher conducted Classroom Action Research. The research focused in improving writing of narrative text. In this research the data were in the kinds of quantitative and qualitative data. The quantitative data were taken by using test, while the qualitative data were taken by using questionnaire, observation, and interview. The result shows that semantic mapping is able to improve students writing competence. From the pre-test, it was shown that the highest score was 6.50, the lowest score was 3.00, and the average score was 4.70. In the end of cycle 1, the researcher conducted post-test, and the result were as follows: the highest score was 7.00, the lowest score was 5.00, and the average score was 6.20. At the second post-test which was held after cycle 2, the highest score was 8.00, the lowest score was 6.00. and the average was 7.00. Based on the qualitative data anlysing, teaching learning process was held effectively. The class atmosphere was alive, the students were motivated, excited and active in joining the class, the effective communication was occured, and the classroom assesment and reflection ran well.Â Key words: semantic mapping, writing skills, classroom action research.